Retrobulbar Hematoma in Blow-Out Fracture after Open Reduction - Cheon, Ji Seon; Seo, Bin Na; Yang, Jeong Yeol; Son, Kyung Min (Archives of Plastic Surgery, 2013)
Retrobulbar hemorrhage, especially when associated with visual loss, is a rare but significant complication after facial bone reconstruction. In this article, two cases of retrobulbar hematoma after surgical repair of blow-out fracture are reported. In one patient, permanent loss of vision was involved, but with the other patient, we were able to prevent this by performing immediate decompression after definite diagnosis. We present our clinical experience with regard to the treatment process and method for prevention of retrobulbar hematoma using a scalp vein set tube and a negative pressure drainage system.
Keywords: Orbital fractures; Retrobulbar hemorrhage; Orbit